Pelatihan Peningkatan Kompetensi Mahasiswa dalam Menyusun Administrasi Pembelajaran Menyongsong Program MBKM “Kampus Mengajar” - Fitriawan, Dona (LPPPM STAI Darul Hikmah Bangkalan, 2024)
The Independent Learning Campus Independent Program (MBKM) is a program that provides flexibility for students to improve and enrich their knowledge and skills competition by being directly involved in the real world in learning according to their knowledge and fighting spirit to realize their goals. One of the activities on campus is teaching as a teaching assistant in primary and secondary school education units with a period of time determined by government regulations. The results of the discussion in the study program concluded that students were considered to have not received sufficient provisions to engage directly in carrying out learning in schools, for example, they had not fulfilled several programs or lectures that supported these activities. Therefore, it is deemed necessary to provide training in the form of training to increase student competence. This service activity is carried out in stages: 1) presenting material or theory of making learning devices with assistance by lecturers; 2) teaching practice in small groups called micro teaching. The results of the activities carried out for a weeks concluded that: 1) the students were enthusiastic in participating in the activities; 2) running of teaching and learning practice activities well and smoothly; 3) appreciation of neat and systematic reporting of activities to the dean level